A proposed solution to the problem posed by reduction(s) in osmolyte infusion interval: A theory on the origins of stimulus-functional response pairs in biological systems - Jeff-Eke,Imadol V (PeerJ PrePrints, 2015)
This work follows as a response to a problem posed in a previous work: Effects of Osmolyte Infusion Interval Reductions on the Aggregate Measure of Systemic Failure: for a unicellular system. Here we propose and explore a probable solution to the posed problem of how well a cellular system can tolerate random changes to the frequency of osmolytes infused into an intracellular space of interest. The proposed solution involves the ability of biological systems to anticipate occurrences of imminent challenge stimuli, and by so doing, initiate the required functional response(s) against their [stimuli] effects. By stating anticipatory roles in biological systems, we are suggesting a possible origin for the stimulus-response pairing noted in these systems.
Keywords: Anticipation; Anticipatory associations; High output functional response; Stimulus-functional response pairing; Free osmolytes; Aggregate measure of failure